Profili germinali della laicità. Un excursus storico (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Da Lutero alla Pace di Westfalia. Tra potestas indirecta e tolleranza - 1.1. Il cammino verso il modello laico illuminista. Hobbes, Locke e Spinoza - 2. I fondamenti illuministici della laicità - 2.1 Il contributo di Voltaire e Rousseau alla costruzione della laicità francese - 2.2. La libertà religiosa come nuova componente della laicità. Immanuel Kant - 3. I profili germinali della laicità - 3.1. Rapporto Stato/chiese - 3.2. Rapporto Stato/credenze religiose - 4. Conclusione.Germinal Profiles of SecularismABSTRACT: The principle of secularism, as we usually think about it, is the outcome of sociological and historical events and the direct result of reflections of political morality. The present essay will provide a reflection about the “germinal profiles” of secularism. Starting with the breaking of Christian unity, arising from the Protestant reformation, the essay focuses on the strategy regarding the relations between State and Church, on the one hand, and between State and religious beliefs, on the other.
Keywords: Laicità e pluralismo